Reciprocity and status in a virtual field experiment - Andreas Nicklisch; Tobias Salz (Max Planck Institute for Research on Collective Goods, 2008)
This article reports on a field study that has been conducted in the online computer game World of Warcraft. In a basic labor situation a principal gives an upfront wage to an agent (who is unaware that he is participating in an experiment) and asks him to conduct a real-effort task. The unique characteristic of the virtual world allows us to control for agents' abilities to perform the task and to manipulate the principal's social status. Confirming gift exchange theory, generous wages indeed increase agents' efforts, even controlling for agents' abilities, while the principals' social status influences effort provision probability substantially. We interpret this result such that agents assess the kindness of the wages with respect to the expected principals' wealth.
Keywords: C88; C93; D63; 300; Field experiment; gift-exchange; reciprocity; status; virtual world; Reziprozität; Sozialer Status; Feldforschung; Videospiel; Virtuelle Realität